Research on gender in access to economic resources and labor market of ethnic minorities in Vietnam - Duc, Tran Minh (Technium Social Sciences Journal, 2022)
Based on the results of a survey done in 2019 to collect information on the socioeconomic state of 53 ethnic minorities in Vietnam, as well as some current study findings on economic resources and in the labor market of ethnic minorities, the article aims to provide more solutions for Vietnamese authorities and policymakers in the process of developing and implementing policies for ethnic minority areas. Thereby contributing to the effective and comprehensive promotion of gender equality in ethnic minority areas in the future.